(untitled) (Nigerian Journal of Technology, 2025)
This paper presents findings of an investigation on the applicability of Imotoyewa (IM), Ifonyintedo (IF), and Owode-Ketu (OK) clay from Nigeria, and calcium carbide waste (CCW) as a partial substitute for Ordinary Portland Cement (OPC) in the development of a pozzolanic binder. The CEM II was partially replaced with calcined Ifonyintedo clay (C-IF), calcined Owode-ketu clay (C-OK), and calcined Imotoyewa clay (C-IM) at intervals of 10% up to 50% and CCW was also used to replace C-IM, C-IF, and C-OK and at the same interval in a separate mix. Physicochemical, mineralogical, microstructural, Zeta-sizer analysis, Brunauer–Emmett–Teller (BET) methods, were used for characterization. The Index Strength index (SAI) of the burnt clay (CC), setting times of CEMII-CC, CC-CCW, and compressive strength by partially replacing cement with CC and whole cement replacement using CC with CCW were investigated. Results from the SAI indicated a high pozzolanic effect. C-IF with about 40% kaolinite content gave the highest mortar strength than the control at a substitution level of 20%. Kaolinite on the XRD trace was 34-40wt% in the clays, consistent with BET values. The BET and porosity of the CC were well above OPC while C-IF clay, with the highest kaolin content, had the highest limit. ST tests revealed that in the CEMII-CC and CC-CCW paste; CC and CCW inclusion have a linear relationship with the ST and water content of the paste owing to the pozzolanic reaction and dilution impact. They inhibit cement hydration; thus, their ability to retard could be useful with concrete in hot weather. The C-IF’s reactivity with Ca(OH)2 from CCW and CEM:CIC mortar showed similar and noticeable trends on the FTIR. Results have demonstrated the development of pozzolanic binders from blended cement mortar; calcined clay and CCW mortar.